(untitled) (Journal of Interdisciplinary Insights, 2023)
The rise of digital technologies like smartphones, IoT, artificial intelligence, and machine learning promises substantial changes in how clients and consumers navigate their lives. This study aims to enhance customer management, improve the customer journey’s quality and duration (thus promoting loyalty). The core inquiry revolves around the components and structure of a digital marketing model rooted in customer experience management. Employing a mixed research methodology encompassing qualitative and quantitative techniques. The selection of participants for the qualitative phase was facilitated through the snowball method, reaching saturation point to ensure comprehensive coverage. The quantitative segment of the research, focused on model explanation, entails the collection of data through questionnaires conducted with customers of various digital enterprises. The sample size consisted of 384 individuals selected randomly, following the application of Cochran’s formula. The culmination of this study lies in the extraction of key conditions, contextual factors, intervening elements, observable phenomena, strategic elements, and resultant outcomes that impact the digital marketing model underpinned by customer experience management. Through data analysis techniques, the interconnections between these elements were established, contributing to a comprehensive understanding of the model’s dynamics.